Le Corbeau de Poe et ses traductions françaises - Vacovská, Marta (Verbum – Analecta Neolatina, 2013)
The Raven by Edgar Allan Poe is undoubtedly considered to be one of the most remarkable works of art in the world of poetry. To capture the genius reflected in the poem became a challenge for translators from all over the world. In the context of French literature it was Baudelaire who first offered the translation of this famous poem to French readers. Despite the difficulties caused by the differences of both language systems and perfect premeditation of nearly mathematical composition of the original work, Baudelaire accomplished his task with honour. As a translator, he stays “conform” not only in his intentions to keep the language quality of this poem but he also wants the reader to recognise and appreciate Poe’s talent. However, this literary imperative leads him to the use of the means which belong to the “adaptive” translation method. These adaptations are most conspicuous when observing the musical aspect of the text.